Semiótica e discurso na análise da obra cinematográfica “Polícia Federal: a lei é para todos” - Gonçalves, Elizângela Gomes Quintana (2021)
This dissertation deals with the application of Greimasian Semiotics and Discourse Analysis to examine the interlocutions that engender the cinematographic work “Polícia Federal: a Lei é para todos” (2017), directed by Marcelo Antunes, based on the book of the same name by Carlos Graieb and Ana Maria Santos. Its objectives are: to describe and interpret the “Law” as a protagonist character based on the aforementioned film. Analyze the meanings constructed from the oppositional relations present in the work. Investigate the speeches presented based on the theoretical devices of Discourse Analysis. And to present the interpretations extracted from the film narrative embodied in the intersection between Semiotics and Discourse Analysis. The established methodology is qualitative research with bibliographic support, with a view to articulating concepts to the practice of investigating discourses set in motion in the film construction in question. That said, the theoretical-methodological apparatus employed was structured based on the contributions of Michel Pêcheux (1960, 1983, 1988, 1990, 1997, 2002, 2009 and 2010), Greimas (1973, 1975, 2014), Greimas and Courtes (1979), Fiorin (1995, 2011, 2013, 2016), Diana Luz de Barros (2001, 2002, 2005, 2011, 2012), Orlandi (1983, 1986, 1993, 2007, 2011, 2017) and Soares (2020), among others that were necessary. The results obtained made it possible, through the application of the Generative Sense Path, to extract from the fundamental level the relations of the semantic opposites (honesty versus dishonesty, punishment versus impunibility, partiality versus impartiality, and justice versus injustice). Regarding the narrative level, narrative programs are obtained in which the states of transformation of a state of conjunction were configured for a condition of disjunction with the object of value or vice-versa and from which it was possible to demonstrate the act of man over man. And from the discursive level, corruption became the central theme narrated, from which several others emerged, such as: the investigation of the Lava Jato operation, the culture of dishonesty, the overpricing of public works. In this sense, the application of the law in a convenient way does not live up to the title of the film, as it presents divergence in the light of the narrated facts, in addition to drug trafficking, prostitution, the impartiality of judicial decisions. And from Discourse Analysis, in addition to partially ratifying the results obtained based on the investigation of Semiotic theory, he was able to add interpretations and point out the law as the protagonist of the work through his transfiguration of the representation of the characters, of the delegate, judge, prosecutor and prosecutors. In addition to pointing out the false criticism directed at the antagonistic character, the corruption of the public power as the origin and sole responsible for all social problems, because in addition to this corrupt system, there is the slave system that is updated and reflected by the division of social classes in Brazil.